O18 Causes and impact of incomplete reperfusion in eTICI 2b: insights from the ESCAPE-NA1 trial. (29th August 2022) - Cimflova, P; Kappelhof, M; Singh, N; Sehgal, A; Ospel, JM; Bala, F; Almekhlafi, M; Tymianski, M; Hill, MD; Goyal, M
Abstract : Introduction: The degree of mTICI 2b reperfusion varies from 51%-89% in acute stroke patients treated with mechanical thrombectomy(MT) 1 . Incomplete reperfusion could be due to either focal occlusion (residual thrombus, fragmented/migrated thrombus) or slow flow 2 . With advancing endovascular techniques, residual distal/medium vessel occlusions can be targets for MT or intra-arterial thrombolysis 2, 3 . Aim: We investigated the causes of IR and evaluated whether they could be a target for MT. Secondarily, we assessed the proportion of incomplete reperfusion leading to infarction on follow-up imaging. Methods: Patients from the ESCAPE-NA1 trial with final mTICI 2b were included. Residual occlusions were evaluated on the final DSA run. The potential targets for MT were assessed as follows: a) single MT-accessible occlusion, b) single MT-accessible occlusion+multiple small non-MT-accessible occlusions, c) single non-MT-accessible occlusion, d) multiple small/non-MT-accessible occlusions or slow flow. Infarction in the incomplete reperfusion territory was assessed on follow-up CT/MR. Results: Of 1105 patients in ESCAPE-NA1, 443(40.1%) were included with a median of 1 MT pass (IQR1–2). A single MT-accessible occlusion was found in 61/443 cases (13.8%), a single MT-accessible occlusion + multiple small non-MT-accessible occlusions in 86/443(19.4%), a single non-MT-accessible occlusion in 36/443(8.1%), and multiple small non-MT-accessible occlusions or slow flow in 260/443 cases (58.7%). Overall, incomplete reperfusion was associated with infarction in 238/443 cases (53.7%), no infarction in 104/443(23.5%) and impact of incomplete reperfusion was undetermined in 101 cases (22.8%) due to large underlying M1-MCA infarct. Conclusion: Incomplete reperfusion was most often caused by multiple small non-MT-accessible occlusions and was associated with development of infarct on follow-up imaging in more than half of the patients. References: Tung EL, Mctaggart RA, Baird GL, et al . Rethinking Thrombolysis in Cerebral Infarction 2b: which Thrombolysis in Cerebral Infarction Scales Best Define Near Complete Recanalization in the Modern Thrombectomy Era? Stroke; A Journal of Cerebral Circulation 2017;48 (9):2488–93. Kaesmacher J, Ospel JM, Meinel TR, et al . Thrombolysis in Cerebral Infarction 2b Reperfusions: To Treat or to Stop? Stroke 3461–3471. Goyal M, Ospel JM, Menon BK, Hill MD. Mevo: The Next Frontier? J Neurointerv Surg . 2020;12 (6):545–547 Do you have any conflict of interest to declare? : No